(untitled) (Bangladesh Journal of Plant Taxonomy, 2021)
In this study, the pollen morphology and exine structure of nine species of the genus Salvia L. (Lamiaceae) were investigated using light microscopy and scanning electron microscopy (SEM). Six micromorphological characters (pollen shape, polar length, equatorial width, exine and intine thickness, colpus length and colpus width) of pollen grains of Salvia have been identified. The palynological observations revealed that pollen grains of most studied taxa of Salvia were suboblate shape and possess hekzacolpate aperture. Tectal surface sculpture was a good criterion to identify particular taxa from Salvia. The pollen of which is characterized by reticulate, the pollen ornamentation was similar in all studied taxa. Bangladesh J. Plant Taxon. 28(2): 395-403, 2021 (December)